TWO STEPS AHEAD, ZIGUE-ZAGUE AND FALL - Singer, André (Universidade de Brasília, 2018)
From the debates established at the seminar "The Left in the Present: Dialogues Latin America and Europe", held at the University of Brasilia in October 2017, this text presents a synthesis of the main research findings made by the author between 2012 and 2017